Osteoblasts mineralization and collagen matrix are conserved upon specific Col1a2 silencing - Silvia Maruelli (Matrix Biology Plus, 2020)
Classical osteogenesis imperfecta (OI) is an inherited rare brittle bone disease caused by dominant mutations in the COL1A1 or COL1A2 genes, encoding for the α chains of collagen type I. The definitive cure for the disease will require a gene therapy approach, aimed to correct or suppress the mutant allele. Interestingly, individuals lacking α2(I) chain and synthetizing collagen α1(I)3 homotrimers do not show bone phenotype, making appealing a bone specific COL1A2 silencing approach for OI therapy. To this aim, three different Col1a2-silencing RNAs (siRNAs), −3554, −3825 and −4125, selected at the 3′-end of the murine Col1a2 transcript were tested in vitro and in vivo. In murine embryonic fibroblasts Col1a2-siRNA-3554 was able to efficiently and specifically target the Col1a2 mRNA and to strongly reduce α2(I) chain expression. Its efficiency and specificity were also demonstrated in primary murine osteoblasts, whose mineralization was preserved. The efficiency of Col1a2-siRNA-3554 was proved also in vivo. Biphasic calcium phosphate implants loaded with murine mesenchymal stem cells were intramuscularly transplanted in nude mice and injected with Col1a2-siRNA-3554 three times a week for three weeks. Collagen α2 silencing was demonstrated both at mRNA and protein level and Masson's Trichrome staining confirmed the presence of newly formed collagen matrix. Our data pave the way for further investigation of Col1a2 silencing and siRNA delivery to the bone tissue as a possible strategy for OI therapy.